READING WRITING BY WOMEN - Harry Aveling (Celt: A Journal of Culture, English Language Teaching & Literature, 2006)
Differences in gender may produce differences in style of writing. It is my intension here to show that the style used by female in contrast to male writers results in a number of significant differences. Some of them are caused by the writers cultural background. Being a teacher, I would like to share with others how the gender and feminist theories can be applied to analyze writings by women.